2014
DOI: 10.1007/s00268-014-2582-3
|View full text |Cite
|
Sign up to set email alerts
|

Audit on Preoperative Fasting of Elective Surgical Patients in an African Academic Medical Center

Abstract: Background Preoperative fasting is a requisite before anesthesia. The main reason for preoperative fasting is to reduce gastric volume and acidity and thus decrease the risk of pulmonary aspiration. However, preoperative fasting is usually prolonged beyond the recommended time for various reasons. Despite the many adverse effects of prolonged fasting, patients sometimes fasted for a prolonged time when surgery was delayed for different reasons at the University of Gondar Hospital. The aim of this study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
45
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 17 publications
8
45
0
10
Order By: Relevance
“…Furthermore, although sedative premedications were consistently effective in reducing preoperative anxiety, effects of them on the postoperative behavioral alteration is debatable. 11,12 Although no previous study evaluated interaction between preoperative fasting and ED in this setting, Xar a et al 13 in 2013 reported that prolonged preoperative fasting is a risk factor for postoperative emergence along with postoperative pain and major surgery and Chauvin et al 6 also reported that thirst might be a reason for unsettling behavior in children in the postoperative period. A number of studies 12,14 have reported a significantly longer duration of fasting than recommended by the various society guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although sedative premedications were consistently effective in reducing preoperative anxiety, effects of them on the postoperative behavioral alteration is debatable. 11,12 Although no previous study evaluated interaction between preoperative fasting and ED in this setting, Xar a et al 13 in 2013 reported that prolonged preoperative fasting is a risk factor for postoperative emergence along with postoperative pain and major surgery and Chauvin et al 6 also reported that thirst might be a reason for unsettling behavior in children in the postoperative period. A number of studies 12,14 have reported a significantly longer duration of fasting than recommended by the various society guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of postoperative hunger and thirst in these patients did not correlate with the duration of fasting, as 51.2% of patients who fasted from fluids for ≥9 hours did not experience any thirst postoperatively. [10] Furthermore, the methodology of Cestonaro et al, [11] who conducted a retrospective study in a public university hospital in the south of Brazil, was very similar to ours. Their results showed that the median period of preoperative fasting from solid food was 16 hours and 30 minutes (5 hours and 30 minutes -56 hours and 55 minutes) and from fluids 15 hours and 45 minutes (2 hours and 30 minutes -56 hours and 55 minutes).…”
mentioning
confidence: 96%
“…Gebremedhn and Nagaratnam [10] conducted a cross-sectional study, where 43 patients h00 17h00 18h00 19h00 20h00 21h00 22h00 23h00 00h00 01h00 02h00 03h00 04h00 05h00 06h00 07h00 08h00 09h00 RESEARCH underwent elective surgery. Their methods and results were similar to ours.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[7] In a study done by Gebremendhn EG et al, the mean duration was even higher, being 19.6 hours. [8] Although, the guidelines recommend pre-operative clear fluid intake 2 hours prior to the surgery, the knowledge regarding the definition of clean fluids was lacking among the study participants. Studies have shown discrepancies in the instructions given by anaesthetists and the implementation of this instruction by the nurses in the wards.…”
Section: Discussionmentioning
confidence: 99%